2017
DOI: 10.3136/nskkk.64.132
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Process of a Novel Mozzarella Cheese Using Originally Isolated Lactic Acid Bacteria, <i>Streptococcus salivarius </i>ssp. <i>thermophilus</i>, from Hokkaido

Abstract: To produce a novel Mozzarella cheese, the homofermentative lactic acid bacteria (LAB) Streptococcus salivarius ssp. thermophilus, isolated in Hokkaido, was chosen from the authors< originally constructed LAB library. Physiological analysis of this strain indicated relatively weak acid production. To use this LAB as starter bacteria to produce mozzarella-type cheese, citric acid was used as a supplement to decrease the pH. Thus, the manufacturing method using both lactic acid fermentation and pH adjustment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It also acts synergistically with L. bulgaricus and has been shown to be the safest probiotic [85]. Therefore, based on the results of previous studies and this study, we suggest the therapeutic potential of probiotic formulations based on S. thermophilus and L. bulgaricus, focusing on S. salivarius, for subjects with type P enterotype [86]. Studies have shown that Prevotella and Agathobacter are associated with high protein intake [87,88].…”
Section: Discussionmentioning
confidence: 54%
“…It also acts synergistically with L. bulgaricus and has been shown to be the safest probiotic [85]. Therefore, based on the results of previous studies and this study, we suggest the therapeutic potential of probiotic formulations based on S. thermophilus and L. bulgaricus, focusing on S. salivarius, for subjects with type P enterotype [86]. Studies have shown that Prevotella and Agathobacter are associated with high protein intake [87,88].…”
Section: Discussionmentioning
confidence: 54%